2014
DOI: 10.1097/mib.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Therapeutic Concentration Monitoring of Infliximab May Improve Outcomes for Patients with Inflammatory Bowel Disease

Abstract: Background Infliximab (IFX) is effective in the treatment of inflammatory bowel disease; however, the effect is often not durable. It is unknown if proactive therapeutic concentration monitoring (TCM) of IFX improves outcomes. Methods This is a retrospective observational study examining the use of proactive TCM and titration of IFX to a target concentration for patients with inflammatory bowel disease in clinical remission at a tertiary care center. The primary aim was to describe the clinical course of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(179 citation statements)
references
References 25 publications
5
168
1
4
Order By: Relevance
“…Overlapping of functional symptoms may simulate loss of response. Immunogenicity occurs in 10%-20% of individuals due to formation of antibodies against the anti-TNF drugs (1,3,16,26) . These antibodies are generally lgG type and connect to the reticulum endothelium system, accelerating the clearance of the drug and increasing the risk of loss of response and infusional reactions.…”
Section: (9090) Suspendedmentioning
confidence: 99%
See 1 more Smart Citation
“…Overlapping of functional symptoms may simulate loss of response. Immunogenicity occurs in 10%-20% of individuals due to formation of antibodies against the anti-TNF drugs (1,3,16,26) . These antibodies are generally lgG type and connect to the reticulum endothelium system, accelerating the clearance of the drug and increasing the risk of loss of response and infusional reactions.…”
Section: (9090) Suspendedmentioning
confidence: 99%
“…However, frequently, relapses may not be translated into clinical symptoms (10,19) . A method for evaluating drug's efficacy is necessary, such as the serum level measurement of IFX, as well as antibody research (14,26) . This method can demonstrate low levels of IFX, with negative or low ATI in some patients, who might benefit from therapy optimization, by increasing medication's dose or decreasing administration intervals (11,23) .…”
Section: Introductionmentioning
confidence: 99%
“…They found that patients with infliximab trough concentration of greater than 5 μg/ml had a higher probability of remaining on infliximab (HR 0.1). At 5 years, the probability of remaining on infliximab was 86% in the group with proactive concentration monitoring compared with 52% in the group without proactive monitoring [Vaughn et al 2014]. The active UC trials 1 and 2 (ACT-1 and ACT-2) of infliximab in UC showed that a level of infliximab of 41 μg/ml at week 8 had a positive predictive value for clinical response of 80%.…”
Section: Serum Drug Levels Optimal Serum Targetsmentioning
confidence: 99%
“…Th e use of therapeutic drug monitoring is most commonly measured when patients lose response to therapy. Although not ready for clinical application, an alternative approach may be the use of proactive drug monitoring ( 77 ). Recent data using proactive drug monitoring (using infl iximab in the TAXIT trial) has demonstrated that in patients in remission, adjustment of drug levels that are too low and those that are too high results in a more effi cient use of the drug.…”
Section: Anti-tnf and Anti-integrin Therapymentioning
confidence: 99%